A Study on Fracture Resistance of Tie-Wings and Shear Bond Strength of Srinakharinwirot Aluminum Oxide Ceramic Orthodontic Brackets - Thonggerd, Warut; Wasanapiarnpong, Thanakorn; Didron, Pavinee Padipatvuthikul; Sombuntham, Nonglak (Khon Kaen University Dental Journal, 2020)
The objectives of the study were to find average surface curvature of premolars of Thai samples, to develop Srinakharinwirot (SWU) ceramic bracket by incorporating this curvature into its base and to compare its fracture resistance of tie-wings and shear bond strength with commercial brackets. Buccal surfaces of 40 upper premolars from Thai samples were scanned and averaged into one surface curvature. SWU ceramic bracket was designed by incorporating the derived curvature into its base and fabricated by injection-mold technique. Fracture resistance of tie-wings and shear bond strength was compared between SWU ceramic brackets and commercial brackets. It was found that average buccal surface curvature of upper premolars of Thai samples was less than the commercial bracket base. Analysis by independent t-test showed that fracture resistance of tie wings and shear bond strength were statistically significant lower (p<0.05) in SWU ceramic brackets (48.38 ± 9.95 MPa and 15.01 ± 5.45 MPa, respectively) compared to the controls (126.28 ± 33.96 MPa and 31.76 ± 6.49 MPa, respectively). In conclusion, SWU ceramic bracket was developed using the average buccal surface curvature of upper premolars of Thai samples. Although shear bond strength of SWU ceramic bracket were lower than the commercial brackets, it was found to be clinically acceptable.